Стилістичні засоби при передачі емоцій персонажів та їхній переклад - Bodnarchuk, Anastasiia (Рута, 2021)
The present research focuses on the analysis of the most common stylistic devices that are used to depict characters’ emotions in two novels “Flowers for Algernon” (2006) and “The Minds of Billy Milligan” (1995) written by the American author Daniel Keyes. The patterns of translation of emotionally coloured extracts of the text where these stylistic devices have been used are analysed in this research. As stylistic devices are considered to be an integral part of the composition of works of fiction and they add emotional colouring and exert pragmatic influence on the readers, translators Viktor Shovkun and Olena Stusenko faced onerous work as their task was to find accurate equivalents and use translation transformations in order to avoid literal translation, achieve adequacy on all levels and preserve the stylistic colouring. Furthermore, it is worth mentioning that the translation should fully replace the original text and recipients should perceive the translated text as identical to the original even though stylistic devices and the emotional component of linguistic semantics are arduous to convey in translation. This research also concludes that translators most often resorted to lexical (concretization, generalization and modulation), lexico-grammatical (omission and addition) and grammatical (verbalization and nominalization) translation transformations to avoid literal translation. It has also been established and verified by a comparative method that more stylistic devices are used in the Ukrainian translation than in the original text. The most widely used stylistic devices are metaphors, epithets, comparisons and idioms.
Keywords: стилістичний засіб; перекладацькі трансформації; комунікативний намір; прагматика